Why children differ in motivation to learn: Insights from over 13,000 twins from 6 countries - Kovas, Yulia; Garon-Carrier, Gabrielle; Boivin, Michel; Petrill, Stephen A; Plomin, Robert; Malykh, Sergey; Spinath, Frank M; Murayama, Kou; Ando, Juko; Bogdanova, Olga; Brendgen, Mara; Dionne, Ginette; et al. (Personality and individual differences, 2015)
Little is known about why people differ in their levels of academic motivation. This study explored the etiology of individual differences in enjoyment and self-perceived ability for several school subjects in nearly 13,000 twins aged 9-16 from 6 countries. The results showed a striking consistency across ages, school subjects, and cultures. Contrary to common belief, enjoyment of learning and children's perceptions of their competence were no less heritable than cognitive ability. Genetic factors explained approximately 40% of the variance and all of the observed twins' similarity in academic motivation. Shared environmental factors, such as home or classroom, did not contribute to the twin's similarity in academic motivation. Environmental influences stemmed entirely from individual specific experiences. (übernommen).